ریاستِ مدینہ کے تناظرمیں اِسلامی معاشیات کی اَساسیات: (The Basic Fundamentals of the Islamic Economicsaccording to the State of Madina) - Sayed Kifayat Ullah Shah; Hafiz Saeed Ul Rehman (Seerat Studies, 2023)
This research article “The Basic Fundamentals of the Islamic Economics according to the State of Madina” will discuss the basis of the Economic system of Madina. Economic" plays a vital and very important role in the society. It is a very important part of human life. Islam is a complete way of life. Islam has given complete economics guidance which is called “Islamic Economic System”. Islamic economic system is not only in books, but it has many beautiful and practical examples in the history.The first example was the “State of Madina”. In this state the Holy Prophet (ﷺ) made very clear and strong and fundamentals. The Holy Prophet (ﷺ) defined the sources of economic. He build up the “Finance” totally separate organization. In the State of Madina the Holy Prophet (ﷺ) made the Sahaba able to take part and participate in the Market and business of Madina. He build up “Islamic Economic System” alternate the Jeuses. In the short period of ten years the State of Madina became an economic center for the whole Arab. The Holy Prophet (ﷺ) has forbiddenall the unlawful means of economics like “Interest” etc.